Steady mixed convection flow on a horizontal circular cylinder embedded in a porous medium filled by a nanofluid containing gyrotactic micro0organism - Tham, L.; Nazar, R.; Pop, I. (ASME, 2013)
In this paper, the steady mixed convection boundary layer flow past a horizontal circular cylinder with a constant surface temperature embedded in a porous medium saturated by a nanofluid containing both nanoparticles and gyrotactic micro-organisms in a stream flowing vertically upwards for both cases of a heated and cooled cylinder is numerically studied. The resulting system of nonlinear partial differential equations is solved numerically using an implicit finite-difference scheme. By considering the governing parameters, namely, the mixed convection parameter λ, the bioconvection Lewis number Lb, the traditional Lewis number Le, the bioconvection Péclet number Pb, the buoyancy ratio Nr, the bioconvection Rayleigh number Rb, the Brownian motion Nb, and the thermophoresis Nt, the numerical results are obtained and discussed for the skin friction coefficient, the local Nusselt number, the local Sherwood number, the local density number of the motile micro-organisms as well as the velocity, temperature, nanoparticle volume fraction, and density motile micro-organisms profiles